Binaphthyl–prolinol chiral ligands: design and their application in enantioselective arylation of aromatic aldehydes. Issue 16 (30th March 2021) - Yao, Chao; Chen, Yaoqi; Sun, Ruize; Wang, Chao; Huang, Yue; Li, Lin; Li, Yue-Ming
Abstract : Binaphthyl–prolinol chiral ligands were designed and evaluated with enantioselective arylation of aromatic aldehydes and related reactions. Under optimized conditions, the desired products could be obtained in high yields with up to 99% ee's. Abstract : Binaphthyl–prolinol ligands were designed and applied in enantioselective arylation of aromatic aldehydes and sequential arylation–lactonization of methyl 2-formylbenzoate. Under optimized conditions, the reactions provided the desired diarylmethanols and 3-aryl phthalides in up to 96% yields with up to 99% ee and up to 89% yields with up to 99% ee, respectively. In particular, essentially optically pure 3-aryl phthalides (over 99% ee) were obtained in large quantities through recrystallization.